Functional Screening of Parkinson’s Disease Susceptibility Genes to Identify Novel Modulators of α-Synuclein Neurotoxicity in Caenorhabditis elegans - Vozdek, Roman; Pramstaller, Peter P.; Hicks, Andrew A. (Frontiers in Aging Neuroscience, 2022)
Idiopathic Parkinson’s disease (PD) is characterized by progressive loss of dopaminergic neurons during aging. The pathological hallmark of PD is the Lewy body detected in postmortem brain tissue, consisting largely of aggregated alpha-Synuclein (αSyn). However, an estimated 90 % of PD cases have unknown pathogenetic triggers. Here, we generated a new transgenic Caenorhabditis elegans PD model eraIs1 expressing GFP-based reporter of human αSyn in dopaminergic neurons and exhibits nice readout of developed alpha-Synuclein inclusions in dopaminergic neurons leading to their degeneration during aging. Using these animals in a preliminary reverse genetic screen of >100 PD GWAS-based susceptibility genes we identified together 28 C. elegans orthologs whose inactivation altered eraIs1 phenotype; 10 knockdowns exhibited reduced penetrance of formed αSyn::Venus inclusions in the axons of cephalic (CEP) dopaminergic neurons, 18 knockdowns exhibited increased penetrance of disrupted CEP dendrite integrity of which 9 knockdowns also exhibited disrupted neuronal morphology independently of expressed aSyn reporter. Loss-of-function alleles of the 5 identified genes, such as sac-2, rig-6 or lfe-2, unc-43 and nsf-1, modulated respective eraIs1 phenotypes, respectively, supporting the RNAi data. Western-blot analysis showed that insoluble αSyn::Venus levels do not correlate with the observed phenotypes in these mutants. However, the RNAi of 12 identified modulators reduced formation of pro-aggregating polyglutamine Q40::YFP foci in muscle cells suggesting the possible role of these genes in cellular proteotoxicity. The identified modulators through their associated biological pathways, such as calcium signaling or vesicular trafficking, thus represent new potential therapeutic targets for neurodegenerative proteopathies and other diseases associated with aging.